Small Bowel Perforation Due to Blunt Trauma of Left Leg With an Incarcerated Inguinal Hernia: A Case Report - Shao, Jianli; Sun, Long; Fu, Qinghui (Frontiers in Surgery, 2021)
We report a rare case of a 77 years old man with a known left inguinal hernia presenting with groin pain following a blunt trauma of left leg. Diagnosis of small bowel perforation away from hernia was obtained only in the surgery. Difficulty in preoperative diagnosis, rarity of histologic pattern, and surgical challenges make this case very interesting for surgeons and radiologist. Our message, dealing with situation, is: The diagnosis of small bowel perforation following blunt injury to a non-abdominal trauma is rare and difficult. The association between inguinal hernia and non-abdominal trauma may result in small bowel injuries that normally not appear. Therefore, clinicians should be cautious in treating non-abdominal trauma patients with inguinal hernias.